Aftermath of NSFW in Twitter towards Adolescents / Dewi Seribayu Nordin Selat …[et al.] - Nordin Selat, Dewi Seribayu; Abdul Aziz, Ahlam; Hayat Adnan, Wardatul (Faculty of Communication and Media Studies (FCMS), 2023)
The accessibility to the Internet has shown an increase in adolescents’ use of Twitter for entertainment and informationgathering. At the same time, Twitter has evolved to be a space where NSFW content is widely shared by both the porn industry and individuals who wish to express their individualities. As such, adolescents are at risk of exposure to unsolicited sexual content on Twitter. Adolescents have little to no control when it comes to f iltering explicit sexual content from their accounts on social media. The ubiquitous and borderless nature of social media means that this content can come from anywhere, not just through sharing from friends and families. This paper discusses the prevalence of sexual content on Twitter as well as its impact on adolescents. The f indings have implications for preventative measures seeking to address harmful unsolicited sexual content, including addressing the matter of sexuality in schools and home. The paper uses the scoping review technique as the methodology.